Analysis of image quality and effective dose in adult chest phantom radiography with high BMI - Sanderud, Audun (2018)
Aim: To investigate the impact of different kVp and mAs values on effective dose and image quality using a chest phantom that simulates a normal sized and an obese patient. Methods and materials: A chest phantom with simulated pathological nodules was imaged at various kVp and mAs values. To determine the image quality, CNR and SNR were calculated. An observer study was carried out using relative visual grading with a 3-point Likert scale to assess image quality and nodule visibility. The VGA-study reference image was of the phantom at standard size without the chest plates using 125kVp, 2.4mAs by AEC and 24μSv. Visual grading scores were compared against SNR and CNR values in order to determine the optimal acquisition parameters. Effective dose was calculated using Monte Carlo simulation software, and a Figure of Merit was calculated. Results: The image obtained with 125 kVp and 4.0 mAs had the highest SNR, and the one with 125 kVp and 2.0 mAs had the highest CNR. The observers found that 125 kVp/4.0 mAs was the most optimal image and 125 kVp/6.88 mAs had the least image quality, when compared to the reference image. On calculating the Figure of Merit, 125 kVp/2.0 mAs has the highest score. The effective dose varied from 5.34 μSv to 73.5 μSv for the range of parameters used. Conclusion: It is possible to get higher SNR, CNR and VGA-scores in large sized patient chest radiography at lower mAs than that given by using standard AEC, due to post-processing. Manual mAs better control the image quality than using AEC. Anatomical features are better detected using a higher mAs and a standard kVp. Better image contrast is achieved when a lower kVp and standard mAs is utilised. A protocol for larger patients needs to be tailored accordingly.